The Relationship Between Mothers' Knowledge Level about Posyandu and D/S Coverage - Ariyanti Ariyanti; Islami Islami; Rizki Widyan Aisya (GLOBAL HEALTH SCIENCE GROUP, 2026)
The low coverage of D/S (Simultaneous Arrival and Weighing) at integrated health posts (Posyandu) indicates underutilization of services by mothers of toddlers. Maternal knowledge, as a predisposing factor, plays a significant role in influencing visiting behavior at Posyandus. This study aims to analyze the relationship between maternal knowledge about Posyandus and D/S coverage in the Central Fakfak Community Health Center (Puskesmas) work area. This quantitative study used a cross-sectional design. The study was conducted from July to August 2025 at four Posyandus: Mawar, Kayu Merah Village, Dahlia, Melati, and Krawera, Air Besar Village, Central Fakfak Regency. The study population was all mothers with toddlers registered at these Posyandus. A sample of 70 respondents was determined using the Slovin formula with purposive sampling based on inclusion and exclusion criteria. The dependent variable was D/S coverage. The independent variable was maternal knowledge about Posyandus. Data were collected through a questionnaire that had been tested for validity and reliability, as well as documentation from Posyandu registers for D/S coverage data. Data were analyzed using the Spearman Rank test. The results showed a moderately significant positive correlation between maternal knowledge and D/S coverage in the Central Fakfak Community Health Center Work Area in 2025 (r = 0.36; p = 0.002). The higher the maternal knowledge, the better the coverage of health services received by toddlers, indicating the importance of education and information in improving child health. There is a significant positive correlation between maternal knowledge and D/S coverage in the Central Fakfak Community Health Center Work Area in 2025.